2009
DOI: 10.1503/cmaj.090470
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and harms of erythropoiesis-stimulating agents for anemia related to cancer: a meta-analysis

Abstract: Background: Erythropoiesis-stimulating agents are used to treat anemia in patients with cancer. However, their safety and effectiveness is controversial. We did a systematic review of the clinical efficacy and harms of these agents in adults with anemia related to cancer or chemotherapy. Methods:We conducted a systematic review of published and unpublished randomized controlled trials (RCTs) using accepted methods for literature searches, article selection, data extraction and quality assessment. We included R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(156 citation statements)
references
References 69 publications
7
143
3
3
Order By: Relevance
“…These results are consistent both with those of a recently published, individual patient data-based meta-analysis by the Cochrane Collaboration (Bohlius et al, 2009), which showed no negative effect of epoetin therapy in patients receiving chemotherapy, and with those from a subset of patients receiving chemotherapy in a meta-analysis published by Tonelli et al (2009). In contrast to our results, however, in the overall study population of the meta-analysis published by the Cochrane Collaboration, which included patients not receiving chemotherapy, a detrimental effect on overall survival was observed.…”
Section: Impact Of Baseline Hb Levelsupporting
confidence: 90%
“…These results are consistent both with those of a recently published, individual patient data-based meta-analysis by the Cochrane Collaboration (Bohlius et al, 2009), which showed no negative effect of epoetin therapy in patients receiving chemotherapy, and with those from a subset of patients receiving chemotherapy in a meta-analysis published by Tonelli et al (2009). In contrast to our results, however, in the overall study population of the meta-analysis published by the Cochrane Collaboration, which included patients not receiving chemotherapy, a detrimental effect on overall survival was observed.…”
Section: Impact Of Baseline Hb Levelsupporting
confidence: 90%
“…Inconsist ent results were reported especially in the metastatic setting and by meta analyses [41][42][43]. In contrast, no data were avail able for the adjuvant treatment of breast cancer patients.…”
Section: Specific Sites Of Metastasesmentioning
confidence: 99%
“…Nevertheless, this treatment addresses only the symptoms, not the cause of the anemia. Furthermore, EPO can provoke cardiovascular and thrombo-embolic side effects, as well as possible tumor progression [21][22][23][24]. Indeed, cancer cells in many tumor types express the Erythropoietin receptor (EPOR) [25], and the interaction between Erythropoietin and the EPOR can activate the expression of genes implicated in angiogenesis -5 -hematopoietic cells independently from Erythropoietin deficiency.…”
Section: Introductionmentioning
confidence: 99%